Interstellar [videorecording (Blu-Ray)] - Nolan, Christopher, 1970-; Zimmer, Hans (Warner Bros. Entertainment and Paramount Pictures, 2017)
With our time on Earth coming to an end, a team of explorers undertakes the most important mission in human history: traveling beyond this galaxy to discover whether mankind has a future among the stars.